1994
DOI: 10.1038/ki.1994.77
|View full text |Cite
|
Sign up to set email alerts
|

Site specific regulation in the kidney of endothelin and its receptor subtypes by cyclosporine

Abstract: Endothelin (Et) has been suggested by us and others to play a role in glomerular dysfunction that characterizes cyclosporine (Cs)-associated nephrotoxicity. Since Et exerts its actions through at least two receptor subtypes, and because these receptor subtypes have particular distributions in the renal parenchyma, we investigated changes in mRNA expression for Et and its receptor subtypes in glomeruli and medulla of rats treated with Cs. Polymerase chain reaction coupled with reverse transcription (RT-PCR) met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
3

Year Published

1995
1995
2001
2001

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(29 citation statements)
references
References 23 publications
0
26
0
3
Order By: Relevance
“…Furthermore, the dog basilar artery exhibited an increase in ETB receptor binding sites after experimental subarachnoid haemorrhage (Roux et al, 1995). Increased intracellular calcium due to ETB receptor activation has been seen in aortic smooth muscle cells from spontaneous hypertensive rats as compared with controls (Batra et al, 1993), and rat kidney medulla demonstrated an upregulation of the ETB receptor mRNA after treatment with cyclosporin (Iwasaki et al, 1994). These data together with the present study suggest that the ETA receptor is more static as compared to the ETB receptor, and consequently the regulation of the ETB receptor may have physiological or pathophysiological implications.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the dog basilar artery exhibited an increase in ETB receptor binding sites after experimental subarachnoid haemorrhage (Roux et al, 1995). Increased intracellular calcium due to ETB receptor activation has been seen in aortic smooth muscle cells from spontaneous hypertensive rats as compared with controls (Batra et al, 1993), and rat kidney medulla demonstrated an upregulation of the ETB receptor mRNA after treatment with cyclosporin (Iwasaki et al, 1994). These data together with the present study suggest that the ETA receptor is more static as compared to the ETB receptor, and consequently the regulation of the ETB receptor may have physiological or pathophysiological implications.…”
Section: Resultsmentioning
confidence: 99%
“…Endothelin 1 (ET-1) concentrations are higher in cyclosporin-A-treated patients compared to controls with comparable renal function [61, 62]. The increment in plasma endothelin concentrations is dose-dependent.…”
Section: What Are the Mechanisms Leading To Hypertension In The Graftmentioning
confidence: 99%
“…Quantification of ET-1, ECE-1, and CNP mRNAs was performed using the competitive polymerase chain reaction (PCR) method as previously reported. 21 The sequences of sense and antisense primers for ET-1, 22 CNP, 23 ECE-1, 24 and eNOS 25 were designed as previously reported. The intra-and interassay variabilities of the competitive PCR were 11.9% and 12.9%, respectively, for ET-1, 12.2% and 13.4% for CNP, 12.0% and 13.1% for ECE-1, and 12.3% and 13.9% for eNOS.…”
Section: Competitive Polymerase Chain Reaction For Et-1 Ece-1 and Cmentioning
confidence: 99%